MON-461 A Rare Case of Thyroglobulin Deficiency with Ectopic Thyroid Tissue - Venkataraman, Sandhya (J Endocr Soc, 2020)
Background: The production of thyroglobulin (TG) is initiated by TSH binding to the TSH receptor leading to the transcription and production of TG protein. TG protein then gets transported to the lumen of the follicular cell where its tyrosine amino acids get iodinated and coupled to form T3 and T4. TG deficiency is a rare autosomal recessive genetic condition characterized by congenital thyroid goiter, increased thyroid uptake and primary hypothyroidism. Clinical Case: A 21 year old South Asian female with a history of TG deficiency, hypothyroidism, and thyroid goiter status post thyroidectomy presented with a right sided neck mass. She was diagnosed hypothyroidism with a goiter at the age of five. Levothyroxine replacement was initiated and she had normal growth and development. At the age of ten upon transferring care to our health network, there was concern for enlargement of the goiter. Labs showed TSH of 2.85 uIU/mL (normal: 0.36-3.74 ulU/mL), thyroid binding globulin of 18.2 ug/mL (normal: 13-30 ug/mL), TG antibody less than 20 IU/mL (normal: less than 40 lU/mL) and TG level less than 0.2 ng/mL (normal: less than 55 ng/mL). Thyroid uptake and scan showed overall increased uptake. Genetic studies revealed homozygous mutation of thyroglobulin deficiency. Further history obtained confirmed patient’s parents were first cousins with heterozygous thyroglobulin mutations. Due to enlarging multinodular goiter with thyroid gland measuring 6.2 cm x 4 cm on the right and 6.2 x 3.6 cm on the left, total thyroidectomy was completed in 2012. Pathology showed benign thyroid tissue. In May 2019 the patient skipped levothyroxine replacement due to lapse in prescription refill and TSH increased to 28 ulU/mL. Around that time, she noticed an enlarging right sided neck mass. MRI of the neck showed an enhancing mass posterior to the submandibular gland measuring 1.6 x 1.4 cm. Fine needle aspiration in August 2019, showed a mixed population of lymphocytes and few benign appearing glandular cells. Pathology obtained after resection of the right neck mass in September 2019 revealed benign thyroid tissue with no lymphoid tissue, staining positive for TTF-1 and PAX-8. Conclusion: TG deficiency has an incidence of 1:100,000 live births and is more common in cases of genetic consanguinity. There have been over fifty mutations of varying penetrance identified leading to differing consequences in TG production and processing. These mutations can cause structural changes in the TG protein, decreased tyrosine residue on TG leading to poor iodination and ineffective TG transport within the follicular cell. We propose that the right sided neck mass was regrowth of residual thyroid tissue due to the stimulatory effect of TSH after missed doses of levothyroxine caused TSH elevation. Our case is the first of TG deficiency wherein the patient developed ectopic thyroid tissue proliferation after a period of thyroid hormone deficiency.